Characterization of Philippine honey according to geographic origin using Handheld X-ray Fluorescence Spectrometry - Mutuc, Paolo Jose C.; dL. Francisco, Mario Leonora Lotis; Bautista VII, Angel T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2024)
This study investigated the trace elements found in Philippine bee honey from various geographic origins using a Portable X-ray Fluorescence Spectrometer. Fifty-nine authenticated honey samples were collected from regions 1, 2, 3, 4A, 4B, 5, 6, 8, 11, CAR, and NCR. These samples included honey from Apis breviligula, Apis cerana, Apis dorsata, Apis mellifera, and Tetragonula biroi. Pearson’s Correlation was used to identify relationships between trace element concentrations and particulate matter (PM10) concentration, forest cover, and urban population density in the different regions. Correlational analysis revealed a significant positive association between tungsten concentration in honey and urbanization as well as PM10 with p-values of 0.00022 and 0.00307 respectively. Furthermore, forest cover positively correlated with platinum and aluminum content with p-values of 0.04396 and 0.02593. A comparison of means was also conducted after dividing the regions into areas of high and low degrees of anthropogenic influence. Areas with an urbanization level higher than the national average showed significantly higher concentrations of sulfur and zinc with p-values of 0.020812 and 0.003896 respectively; while higher forest cover showed positive correlation with aluminum and negative correlations with chlorine, potassium, rhodium, and palladium with p-values of 0.030943, 0.0452, 0.048327, 0.04372, 0.024714; however, no significant differences were found between PM10 concentrations. Adjacent regions displayed consistent trace elements, with few significant disparities found in comparative analyses. While the findings suggest anthropogenic influences on honey contamination, limited data on hive proximity to pollution sources and small, regionally skewed sample sizes preclude definitive conclusions. Future research should employ targeting sampling strategies to better ascertain the effects of human-induced contaminants on bee honey.
Thesis (Bachelor of Science in Food Technology) -- University of the Philippines Diliman
Bibliography: pages 48-65.
Keywords: Trace elements -- Philippines; Honey -- Philippines